The Influence of Influencer Marketing Strategy on Generation Z Consumer Purchasing Behavior - Saroyini, Putu; Putri PA, Andiena Nindya (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the digital era, influencer marketing has become one of the main strategies used by companies to influence consumer purchasing behavior among Generation Z, which is the most active demographic group on social media and is highly influenced by content created by influencers. However, there are some specific aspects related to the purchasing behavior of Generation Z consumers that have not been explored in depth. This study aims to explore the influence of influencer type, content type, influencer engagement, and marketing message on Generation Z consumers' purchasing behavior. This study uses a quantitative approach with a survey method, the population is Generation Z consumers in Indonesia who actively use social media and are exposed to content from influencers. The research sample was taken using purposive sampling of 323 respondents, with data collected through questionnaires distributed online. Data analysis used path analysis to identify the relationship between the research variables. The results showed that influencer type, content type, influencer engagement, and marketing message have a significant effect on product awareness, purchase intention, purchase decision, and consumer satisfaction. A well-designed influencer marketing strategy can increase the effectiveness of marketing campaigns and influence the purchasing behavior of Generation Z consumers, with a focus on selecting suitable influencers, developing engaging content, and increasing the engagement and effectiveness of marketing messages to achieve optimal results.